ANALYZING THE IMPACT OF CAR, NIM AND NPL ON ROA OF BANKING COMPANIES (AN EMPIRICAL STUDY ON BEI LISTED COMPANIES) - Yuana Mandagie (FEB-UP Press, 2021)
This research aims to investigate the influence of CAR, NIM, and NPL on ROA of banking companies listed in the Indonesia Stock Exchange (ISX) during the period of 2013 to 2017 in accordance with the criteria of Bank Indonesia. This empirical study employs multiple regression in its data analysis. The model is used to describe the influence of independent variables to the variables simultaneously. The results conclude that the ratio of financial performance in the CAR and NIM banking companies has a positive and significant effect on ROA. This study found that NPL has a significant negative impact on ROA in the banking business while others are positive. Moreover, the higher the CAR and NIM of a bank, it will cause an increase in ROA in the company; the more NPL of a bank increase, the ROA will be decreased. In general, the influence of these three independent variables on ROA in the banking company for 54.6% and included in the category of being.